UPAYA KEPALA MADRASAH DALAM MENINGKATKAN MUTU MADRASAH - Suhaimi Djamal (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
The purpose of this study was to find out the efforts of madrasa heads in improving the quality of madrasas. This study included empirical qualitative research using a field research approach. The steps taken in analyzing were collecting data, data reduction, data presentation, verification (conclusion drawing ). The results of this study indicate that the efforts of Madrasah Heads to Improve Madrasah Quality by conducting Teaching and Learning Activities (KBM) fostering teacher professionalism can indirectly be carried out through seminars, training, further studies, and participation in KKG and MGMP. Second, the development of infrastructure such as the construction of new buildings, renovation of old buildings, construction of fences, and improvement of other spaces so as to enhance the learning process and the potential of students. In improving teacher performance, madrasa heads always increase teacher commitment in realizing discipline, intensely motivating teacher work, and being a role model for teachers in their madrasah environment.